(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2010)
DIRETORA DA REVISTA Desembargadora Federal Eva Regina Turano Duarte da Conceição JORNALISTA RESPONSÁVEL Rosana Sanches (MTb 17993) EQUIPE Francisco Oliveira da Silva Lucia Massako Y. C. Rosa Maria José Francisco da Rocha Renata Bataglia Garcia